Quaternized diaminobutane/poly(vinyl alcohol) cross-linked membranes for acid recovery via diffusion dialysis - Ashraf, Muhammad Adnan (MDPI, 2021)
Diffusion dialysis (DD) using anion exchange membranes (AEM) is an effective process for acid recovery and requires the preparation of suitable materials for AEMs, characterized by unique ions transport properties. In this work, novel AEMs composed of quaternized diaminobutane (QDAB) and poly(vinyl alcohol) (PVA) were cross-linked by tetraethoxysilane (TEOS) via the sol-gel process. The prepared AEMs were systematically characterized by Fourier-transform infrared (FTIR) spectroscopy, ion-exchange capacity (IEC) analysis, thermo gravimetric analysis (TGA), water uptake, linear expansion ratio (LER), and mechanical strength determination, scanning electron microscopy (SEM), and DD performance analysis for acid recovery using a hydrochloric acid/iron chloride (HCl/FeCl2) aqueous mixture and varying the QDAB content. The prepared AEMs exhibited IEC values between 0.86 and 1.46 mmol/g, water uptake values within 71.3 and 47.8%, moderate thermal stability, tensile strength values in the range of 26.1 to 41.7 MPa, and elongation from 68.2 to 204.6%. The dialysis coefficient values were between 0.0186 and 0.0295 m/h, whereas the separation factors range was 24.7-44.1 at 25 degrees C. The prepared membranes have great potential for acid recovery via diffusion dialysis.